System Motor Gearbox Control For Increase Accuracy Angle On CPM Elbow Tool PID Method - Kurniawan, Desi Dwi; Ariswati, Her Gumiwang; Lamidi; Sumber (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2025)
Continuous Passive Motion (CPM) is a rehabilitation tool designed to help joint recovery after surgery by passively moving the joint within a certain range of motion. Previous studies have used the ATmega8535 microcontroller with a PWM system. In this study, a control system was developed using Proportional-Integral-Derivative (PID) to improve the angular accuracy of the CPM tool specifically for the elbow joint. The implementation of PID aims to control the gearbox motor to achieve angles of 45°, 90° and 130° which drive the CPM tool so that it can operate with high accuracy and adjust the angle according to the desired therapy settings. This tool using Encoder sensor to detect corner movement joints in real-time. The Arduino Uno microcontroller controls the motors based on feedback from the sensors and optimizes movement through PID control . Research results show that PID system can increase accuracy corner with a low average error . In addition , the system is also equipped with with measurement current using the ACS712 sensor for ensure stability Power during operation . Result of study This can read 45°, 90° and 130° angles with a good level of accuracy , besides it is also capable operated with speed of 40°/ min , 90°/ min , 150°/ min , 210°/ min and 270°/ min . In the measurement readings on the compared devices with Goniometer there is difference error at 45° angle is 5°, 90° angle is 1° and 130° angle is 5°. for measurement current on the device the obtained stable value​ 2.5mA.Research This succeed reach optimization control angle on the CPM tool with level good accuracy , so that can support the rehabilitation process patient with more effective and efficient .